2020
DOI: 10.1186/s13229-020-00399-2
|View full text |Cite
|
Sign up to set email alerts
|

Developmental vitamin D deficiency increases foetal exposure to testosterone

Abstract: Background Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders which are more common in males. The ‘prenatal sex steroid’ hypothesis links excessive sex-steroid exposure during foetal life with the behavioural differences observed in ASD. However, the reason why sex steroid exposure may be excessive remains unclear. Epidemiological studies have identified several environmental risk factors associated with ASD, including developmental vitamin D (DVD) deficiency. We have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…As juveniles or adults, offspring have social behavioural deficits and alterations in stereotyped behavioural phenotypes of relevance to autism [ 5 , 80 ]. Interestingly, vitamin D deficiency leads to subtle increases in testosterone levels in maternal blood [ 81 ], a finding which has long-been considered a risk-modifying factor in autism [ 82 ]. Additionally, foetal male brains from vitamin D deficient dams have increased testosterone compared to control males.…”
Section: Developmental Vitamin D Deficiency Effect On Brain Function ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As juveniles or adults, offspring have social behavioural deficits and alterations in stereotyped behavioural phenotypes of relevance to autism [ 5 , 80 ]. Interestingly, vitamin D deficiency leads to subtle increases in testosterone levels in maternal blood [ 81 ], a finding which has long-been considered a risk-modifying factor in autism [ 82 ]. Additionally, foetal male brains from vitamin D deficient dams have increased testosterone compared to control males.…”
Section: Developmental Vitamin D Deficiency Effect On Brain Function ...mentioning
confidence: 99%
“…Additionally, foetal male brains from vitamin D deficient dams have increased testosterone compared to control males. This study went on to show silencing of the major enzyme involved in testosterone breakdown, aromatase, by hypermethylation of its promoter in the brain may be the mechanism [ 81 ].…”
Section: Developmental Vitamin D Deficiency Effect On Brain Function ...mentioning
confidence: 99%
“…Gestational vitamin D deficiency in mice leads to increased maternal corticosterone levels and down-regulation of placental enzymes which inactivate maternal corticosterone [58]. However, we have consistently observed no effect of vitamin D deficiency on baseline corticosterone levels in pregnant rats [59,60]. Thus, differences between placental architecture and/or hypothalamic-pituitary-adrenocortical axis activation may explain the absence of preeclampsia phenotypes between species when subjected to gestational vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, a condition of 25(OH)D deficiency, both maternal and in early childhood, could contribute to abnormal brain development favoring ASD onset with a higher incidence in males [11,31]. Accordingly, recent experimental data confirmed that 25(OH)D deficiency increases testosterone levels in maternal blood and male embryonic rat brains [32]. Therefore, a 25(OH)D deficient status could represent a predisposing factor for ASD onset, increasing foetal exposure to testosterone.…”
Section: (Oh)d Anthropometric Data and Annual Rhythm Cyclementioning
confidence: 98%